Eager, pragmatic or reluctant: Can common Finno-Ugric ethnic and linguistic links substantiate intra-EU CFSP co-operation? - Umut Korkut (Center for Social and Economic Research (CASE), 2008)
The paper discusses the salience of the Finno-Ugric links in substantiating intra-EU cooperation among Finland, Estonia and Hungary. The focus is on investigating evidence of such cooperation in the EU's human rights and minority rights related policies towards the Russian Federation and other eastern neighbourhood states. The paper gives an account of institutionalised forms of cultural and political co-operation among the three countries under study. It discusses whether small EU states can coalesce under constructive policy alliances or not. The paper presents the current foreign policy narratives in Finland, Hungary and Estonia and locates the Finno-Ugric narrative in this general framework.
Keywords: Y80; 330; Finland; Hungary; Estonia; Finno-Ugrism; EU; ENP; CFSP; Internationale Zusammenarbeit; Außenpolitik; Internationale Sicherheit; EU-Politik; Finnland; Ungarn; Estland